Antifouling properties of amphiphilic poly(3-hydroxyalkanoate): an environmentally-friendly coating. Issue 8 (14th September 2021) - Guennec, A.; Brelle, L.; Balnois, E.; Linossier, I.; Renard, E.; Langlois, V.; Faÿ, F.; Chen, G. Q.; Simon-Colin, C.; Vallée-Réhel, K.
Abstract: The development of biofouling is a major problem for marine industries. The conception of antifouling and fouling release coatings, with controlled physical-chemical properties is a promising strategy. Among them, amphiphilic systems, such as those composed of a hydrophobic polydimethylsiloxane matrix and a hydrophilic polyethyleneglycol additive are the most efficient and up to date. Despite their effectiveness, these systems are questioned due to the petrochemical origin of PDMS. The aim of this project was to substitute the PDMS matrix with a biopolymer, poly(3-hydroxybuyrate-co-3-hydroxyvalerate) and to improve its anti-adhesion properties through the elaboration of an amphiphilic system, via the addition of PEG or PHBHHx- b -PEG copolymer. The results, including the physico-chemical properties of PHBHV based coatings and static adhesion tests on a marine bacterium, Bacillus 4J6 and a diatom, Phaeodactylum tricornutum are compared with those of PDMS and PEG-modified PDMS coatings. Real antiadhesion activity was obtained for the PHBHV/PHBHHx- b -PEG system for a promising eco-friendly strategy.